2011
DOI: 10.1159/000324528
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Study on Hepatitis B Virus Infecting Human Choriocarcinoma JEG3 Cells and Its Mechanism

Abstract: Aim: To build a hepatitis B virus (HBV)-infected human trophoblast cell model in vitro and determine the mechanism of intrauterine HBV infection. Methods: Serum from hepatitis B-infected patients containing HBV DNA >109 was drawn, subsequently inoculated into human trophoblast cells in vitro (JEG3) and passage-cultured. The supernatants and intracellular HBV viral load of inoculated cells were tested by real-time PCR, and HBV DNA was determined by Southern blot. Results: From inoculation of the 1st … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…This cell line maintains characteristics of first trimester trophoblast cells (Matsuo and Strauss 1994) and has been used to assess biological effects of exposures to environmental toxicants (Bergemann et al 2003; Canettieri et al 2008; Ding et al 2011; Koc et al 2003; Matscheski et al 2006; Adebambo et al 2015; Guan et al 2013; Kummu et al 2012; Alvarez and Chakraborty 2011). Cells were grown in Dulbecco’s Eagle Minimum Essential Media with 10% FBS, sodium pyruvate, and penicillin/streptomycin at 37°C with 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…This cell line maintains characteristics of first trimester trophoblast cells (Matsuo and Strauss 1994) and has been used to assess biological effects of exposures to environmental toxicants (Bergemann et al 2003; Canettieri et al 2008; Ding et al 2011; Koc et al 2003; Matscheski et al 2006; Adebambo et al 2015; Guan et al 2013; Kummu et al 2012; Alvarez and Chakraborty 2011). Cells were grown in Dulbecco’s Eagle Minimum Essential Media with 10% FBS, sodium pyruvate, and penicillin/streptomycin at 37°C with 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…However, they did not investigate the presence of HBV receptors on these cells 7 . Later, other study also provides the cell models of trophoblasts to study the mechanism associated with transplacental route 22 . Though the previous studies provide evidences that HBV can cross the trophoblast barrier of placenta indicated by the presence of HBV DNA, HBcAg and HBsAg but the clear evidence of replication of HBV in placenta is lacking 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that HBV could infect a variety of primary and passage cells in vitro successfully, among which there are many reports about trophoblast cells [17][18][19] . Our research group has successfully constructed a platform for HBV infecting granular cells in vitro, and the technology is mature [4] .…”
Section: Discussionmentioning
confidence: 99%